Mucocele management in pediatric patients: Penatalaksanaan mukokel pada pasien anak - Rona Liansari Samad; Abul Fauzi; Moh. Gazali (Makassar Dental Journal PDGI Makassar, 2024)
Mukocele is the most common benign lesion of the oral cavity that develops as a result of retention or extravasation of mucus from the minor salivary glands. The aetiology generally stems from trauma or habitual lip biting. This article presents a case de-monstrating the treatment of lip-biting mucocele using surgical excision under local anaesthesia. A 10-year-old boy came with his mother to Hasanuddin University Teaching Dental and Oral Hospital with a complaint of a lump on the lower lip that was felt since about 2 months ago. Initially the lump was small then enlarged to its current size, no pain and no bleeding. Clinical exami-nation found a round-shaped lump on the lower lip with a size of about 1x0.9x0.5 cm with a rubbery consistency, painless, pa-ler colour than the surrounding tissue. The lesion was diagnosed as mucocele and surgical excision treatment under local anaes-thesia is one of the good options for children in treating mucocele, thus preventing recurrence. It was concluded that trauma due to lip biting can lead to mucocele. Surgical excision in mucocele cases is a good definitive treatment in paediatric patients.